Enhanced activity of plasma catalysis for propane decomposition via metal-support interactions of Pt/CeMnyOx - Shi, Yuliang; Li, Jing; Wang, Qiuling; Yao, Shuiliang; Wu, Zuliang; Gao, Erhao; Wang, Wei; Zhu, Jiali; Li, Licheng; Wu, Nanhua (Separation and purification technology, 2024)
[Display omitted] •Support has a great impact on plasma catalytic oxidation of propane.•Strong metal-support interactions govern the synergistic performance of Pt/CeMnOx.•Plasma activates oxygen whilst exciting the oxidation ability of Pt/CeMnOx.•Intermediates can be rapidly oxidized on surface of Pt/CeMnOx assisted with plasma.•Synergistic mechanism of propane decomposition by Pt/CeMnOx is proposed. The elimination of light alkanes has been the subject of extensive research. Rational tuning of the surface electronic structure of catalysts can optimize the adsorption and activation behavior of reactant molecules. Therefore, the role of metal-support interactions in plasma catalysis deserves in-depth investigation. In this study, a simple strategy was employed to synthesize Pt-based catalysts loaded on Ce-based binary oxide supports. The interactions between Pt noble metal and supports were regulated by varying the metal element type of the supports and the ratio of the support metal elements. Among them, 0.3 %Pt/CeMn0.2Ox catalyst was the most effective for the synergistic plasma degradation of propane. Various characterizations showed that the redox ability and Pt species dispersion of 0.3 %Pt/CeMn0.2Ox catalyst were significantly enhanced by strong metal-support interactions. It induced more Pt0 and Ce3+ on the surface for the activation of oxygen or water vapor to generate surface reactive oxygen species. Moreover, the plasma in turn facilitated the electron transfer of Pt/CeMn0.2Ox catalyst and enhanced the metal-support interactions. The reactive oxygen species generated by plasma participated in the oxidation of propane and the oxygen cycle of Pt/CeMn0.2Ox catalyst, thus enhancing the synergistic catalysis. The present work provides insight into the design of catalysts with high plasma catalytic synergy.